Localizing the Global and Globalizing the Local: Opportunities and Challenges in Bali Island Tourism Development - Darma Putra, I Nyoman (Jurnal Kajian Bali (Journal of Bali Studies), 2013)
Abstract In September and October 2013, only one week apart,Bali hosted two global events in the upper class markettourism resort Nusa Dua. The first event was the MissWorld beauty pageant, and the other one was the APECSummit. Thousands of journalists from all over the worldcovered these events. From a tourism marketing point ofview, these two prestigious events helped Bali boost itspopularity through global mass media. Historically, sincethe early phase of its development, Bali’s tourism industryhas received many benefits from global forces initiallychanneled out through the Dutch colonial power in the firstdecade of the twentieth century and later through nationaland multinational corporations. The recent enlisting byUNESCO of Bali’s cultural landscape as a world heritagesite (2012) provides yet another great example of how Balicontinues to receive global endorsement by world institutions as a unique tourism destination. This paper discusesopportunities and challenges caused by globalizationand localization phenomena in the management of Bali’stourism island destination. Bali’s experiences provide aninteresting example of how global and local stakeholdersdevelop the island tourism in a sustainable manner whileat the same time continuing to preserve its local arts andculture as one of its main attractions. While there aremany examples how both forces contribute to numerousopportunities toward the development of Bali’s tourism,it is also true to state that impacts of globalization causesvarious forms of distraction for the island’s ability to takefull control of its vast move of development.
Keywords: Bali, globalization, localization, tourism development, Balinese culture